Effect of Earthing up and Level of Irrigation on Yield and Quality Seed Production of Onion - Ali, MK; Alam, MN; Barkotulla, MAB; Khandaker, SMAT; Simon, PW (Progressive Agriculture, 2014)
A field experiment was conducted during the period from October 2001 to April 2002 to study the effect of earthing up and level of irrigation on yield and quality seed production of onion (cv. Taherpuri) at Rajshahi University campus, Rajshahi, Bangladesh. Two different factors were considered, factor (A): Earthing up (E1), without earthing up (E0) and factor (B): irrigation level (5 levels) viz. irrigation start at 1st time and when required (I4), irrigation start at 40 DAP and when required (I3), irrigation start at 60 DAP and when required (I2), irrigation start at 80 DAP and when required (I1), no irrigation or control (I0). The standard dose of cowdung and NPK were applied according to HRDP (1995). The factorial experiment was laid out following at Split Plot Design (SPD) with three replications. The result revealed that bulb emergence, plant height number of leaves, length of scape, tillers, seeded fruits, fruits set, days to blooming, seed yield, 1000-seed weight and germination percentage were significantly influenced by different treatments. The highest seed yield (405.97 kg/ha) was found from earthing up with irrigation start at first time and when required (E1I4) followed by E1I3 (347.37 kg/ha), E0I4 (330.73 kg/ha) compared with other treatments. The results suggested that earthing up with 3-4 times irrigation is more effective for onion seed production in Bangladesh. DOI: http://dx.doi.org/10.3329/pa.v18i2.18163 Progress. Agric. 18(2): 81 - 91, 2007